IMPLEMENTATION OF REGIONAL REGULATION NUMBER 10 OF 2013 ABOUT SUSTAINABLE COMPLETE CLASS SYSTEM IN GOWA DISTRICT - Arif, Fauziah Nur Hikmah; Sakawati, Herlina; Rukmana, Novayanti Sopia; Aina, Asri Nur (Universitas Negeri Makassar, 2025)
This research aims to find out how the implementation of Regional Regulation Number 10 of 2013 concerning the Sustainable Complete Class System Policy in Gowa Regency is carried out. To achieve this goal the researcher used data collection techniques through observation, interviews and documentation. Data obtained from research results are processed using qualitative analysis by revealing the problem or situation or event as it really is so as to reveal the true facts of the object under study.The results of the research show that the implementation of Regional Regulation Number 10 of 2013 concerning the Sustainable Complete Class System Policy in Gowa Regency has been carried out well. Judging from the 3 main indicators of implementation according to Daniel A. Mazmanian and Paul Sabatier which are quoted in (Suwitri 2008), including: Tracbility Variable of the Problem (Level of Simplicity of the Problem) in this case the Implementation of the Sustainable Complete Class System Policy in Gowa Regency has implemented well in accordance with Regional Regulation No. 10 of 2013 concerning SKTB, Ability of Statue To Structure Implementation (Ability of Laws to Structure the Implementation Process) where the ability of legislation to implement SKTB has a big influence in structuring an implementation process, Nonstatutory Variables Affecting Implementation (Variables Outside the Law that Influence Implementation) still lacks support and understanding among some people regarding the SKTB policy.Dependent Variables or Stages in the Implementation Process also determine the success of implementing Regional Regulation Number 10 of 2013 which discusses the implementation of SKTB so that the implementation of the SKTB program can run well